2021
DOI: 10.3233/jnd-200598
|View full text |Cite
|
Sign up to set email alerts
|

Therapies for Genetic Forms of Parkinson’s Disease: Systematic Literature Review

Abstract: Parkinson’s disease (PD) is a disabling neurological condition characterized by the loss of dopaminergic neurons. Currently, the treatment for PD is symptomatic and compensates for the endogenous loss of dopamine production. In cases where the pharmacological therapy is only partly beneficial or results in major wearing-off complications, surgical interventions such as deep brain stimulation may be an alternative treatment. The disease cause often remains unknown, but in some patients, a monogenic cause can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…In addition, the coexistence of atypical non-dopaminergic signs (89% with postural instability and 83% with dystonic/pyramidal features), precluded a complete motor response to dopaminergic therapy [ 48 ]. Over et al reported similar results in a more recent study [ 272 ]. Among 82 out of 146 SNCA carriers for whom treatment information was available, 79.3% of patients displayed a good response on relative low mean doses of Levodopa, nearly 10% showed a moderate response to higher doses, and 11% had a minimal response [ 272 ].…”
Section: How Genetic Status Can Help In the Current Clinical Manageme...supporting
confidence: 71%
See 3 more Smart Citations
“…In addition, the coexistence of atypical non-dopaminergic signs (89% with postural instability and 83% with dystonic/pyramidal features), precluded a complete motor response to dopaminergic therapy [ 48 ]. Over et al reported similar results in a more recent study [ 272 ]. Among 82 out of 146 SNCA carriers for whom treatment information was available, 79.3% of patients displayed a good response on relative low mean doses of Levodopa, nearly 10% showed a moderate response to higher doses, and 11% had a minimal response [ 272 ].…”
Section: How Genetic Status Can Help In the Current Clinical Manageme...supporting
confidence: 71%
“…Among 82 out of 146 SNCA carriers for whom treatment information was available, 79.3% of patients displayed a good response on relative low mean doses of Levodopa, nearly 10% showed a moderate response to higher doses, and 11% had a minimal response [ 272 ]. In both studies, no obvious differences emerged according to mutation type, but good levodopa responsiveness was more frequently observed in SNCA duplication and triplication carriers compared to p.G51D mutation carriers, despite a higher rate of motor and non-motor adverse events (dystonia, dyskinesias, hallucinations, psychosis) [ 48 , 272 ].…”
Section: How Genetic Status Can Help In the Current Clinical Manageme...mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed the heritability of impulse control disorder was estimated at 57%, suggesting a predominant genetic component [ 197 ]. In contrast, in a retrospective study of people with PD looking at the time to develop L-DOPA induced motor complications, addition of genotype to clinical data did not lead to any improvement in the model [ 198 ].…”
Section: Therapeuticsmentioning
confidence: 99%